The Roles of Floral Organ Genes in Regulating Rosaceae Fruit Development - Yao, Jia-Long; Kang, Chunying; Gu, Chao; Gleave, Andrew Peter (Frontiers in Plant Science, 2022)
The function of floral organ identity genes, MADS-box and APETALA2 (AP2), in flower development is highly conserved across angiosperms. Emerging evidence shows that these genes also play important roles in the development of the fruit that originates from floral organs following pollination and fertilization. However, their roles in fruit development may vary significantly between species depending on the floral organ types contributing to the fruit tissues. Fruits of the Rosaceae family develop from different floral organ types depending on the species, for example, peach fruit flesh develops from ovary tissues, whereas apple and strawberry fruit flesh develop from non-ovary tissues, the hypanthium and receptacle respectively. In this review, we summarise recent advances in understanding floral organ gene function in Rosaceae fruit development and analyse the similarities and diversities within this family as well as between Rosaceae and the model plant species Arabidopsis and tomato. We conclude by suggesting future research opportunities using genomics resources to rapidly dissect gene function in this family of perennial plants.